The Elder Brother, Virgil’s De apibus, and the Chronology of the Plays in the Canon of John Fletcher and His Collaborators, 1617–20 - Lovascio, Domenico (Early Theatre, 2024)
This article argues that John Brinsley's 1620 translation of Virgil's Georgics, Book IV, is a source for John Fletcher and Philip Massinger's The Elder Brother. This contention results in dating the play to 1620 rather than 1618 as suggested by Martin Wiggins. The re-dating has consequences for the dating of other plays in the canon of Fletcher and his collaborators for the period 1617 to 1620, and I propose a new chronology for the Fletcher plays in this time span.